Importance of the research group in the nursing student training - Isabelle Campos de Azevedo; Rita de Cássia Lira da Silva; Diana Paula de Souza Rego Pinto Carvalho; Giovanna Karinny Pereira Cruz; Jéssica Valeska Herculano Lima; Marcos Antonio Ferreira Júnior (Universidade Federal de Santa Maria, 2018)
Aim: to describe and discuss the experiences and importance of the research group for the Nursing student training. Method: experimental report study, which addresses the role of the group for professional training and nursing research and presents the contributions that this space of knowledge construction provides to its members. Results: the members of the group are instigated to have a critical thinking and to have the opportunity to relate the knowledge acquired in the university with the experiences in real working contexts and in the nursing praxis through the research projects, which awakens the reflexibility on diverse contexts. Final considerations: involvement in Research Groups allows and facilitates the advancement of knowledge production, which increasingly distances nursing from the old paradigm of "technique through technique" and allows the action of a thoughtful/reflective practice.